Penerapan Data Mining Untuk Memprediksi Penjualan Buah Dan Sayur Menggunakan Metode K-Nearest Neighbor (Studi Kasus : PT. Central Brastagi Utama) - Ayu Azlina Putri (STMIK Budi Darma, 2021)
PT. Central Brastagi Utama is a supermarket that sells many consumer products including fruits and vegetables. There are many types of quality fresh fruit and vegetables that come from within and outside the country. Unfortunately, so far there is no system that regulates predictions or forecasts for fruit and vegetable sales at PT. Central Brastagi Utama. So that there is often an accumulation of goods, damaged and rotten goods, or even a shortage of goods that results in losses for the company. To solve this problem, a forecasting or Forecasting is needed. Then the Data Mining technique is used with the K-Nearest Neighbor method. It is hoped that using this technique can process the last 3 years of data into information that can help the company in providing stock of goods. The results of this research are the prediction of sales of a number of products, and determine which category of product sales are in demand, moderate or little.